Boarding House Business Conception in the Perspective of Sharia Economic Law - Herlina Herlina; Dwi Noviani; Witry Octasari (Yayasan Adra Karima Hubbi, 2024)
The boarding house business is synonymous with a risky type of business because it deals with daily interactions with people of various habits and backgrounds. The purpose of this study is to describe the development of a boarding house business that is based on Islamic Sharia and meets the provisions of Sharia Economic Law. Measurement and analysis of research data are qualitative in nature, with a comparative level of explanation. Types and research strategies include phenomenology and are classified as field research. Data collection and analysis techniques used participant-observer forms and in-depth interviews accompanied by documents. The results of the study found a boarding business concept that is of good quality and in accordance with the rules and principles of Islamic economic law. The implementation of a boarding house business that is oriented towards the goals of the world and the hereafter begins with honesty, trust, responsibility, and consequences between the owner and the user of the boarding house. Determination of discipline according to the provisions of Islamic sharia must be carried out properly and correctly by both parties without exception, in the form of implementing the rules set by the boarding house owner, including discipline in visiting time, limiting visiting people, tolerance for shared facilities, helping each other in difficulties or making the environment around the boarding house a family sphere, coordinating in various activities out of the ordinary, and supporting each other in every positive activity. The conclusion of the study is that there is openness to all activities related to the benefit of the people.